Observational, prospective, phase 4 study in patients with first‐line recurrent and/or metastatic squamous cell carcinoma of the head and neck treated with cetuximab and platinum‐based therapy: DIRECT. Issue 2 (22nd June 2021) - Guigay, Joël; Chamorey, Emmanuel; Lefebvre, Gautier; Rotarski, Maciej; Wagner, Jean‐Philippe; Blot, Emmanuel; Alfonsi, Marc; Seronde, Audrey; Schulten, Jeltje; Peyrade, Frédéric; Le Tourneau, Christophe
Abstract: Background: Cetuximab plus platinum‐based therapy (PBT) followed by cetuximab maintenance until progression (EXTREME) is a guideline‐recommended first‐line treatment option in recurrent/metastatic squamous cell carcinoma of the head and neck (R/M SCCHN). DIRECT (Dose Intensity RElative to CeTuximab) was the first phase 4 observational study evaluating EXTREME administration in the real‐world setting. Aims: The primary aim of this study was to assess the relative dose intensity of cetuximab in patients with R/M SCCHN treated with first‐line cetuximab according to the EXTREME regimen. Methods and results: Patients were ≥18 years old and eligible to receive cetuximab/PBT. Primary endpoint was cetuximab relative dose intensity (RDI). Of prospectively enrolled patients ( n = 157), 119 received ≥1 cycle of EXTREME. Practices differing from the EXTREME trial were 5‐fluorouracil omission (14%), maintenance cetuximab given every other week (54%), prior cetuximab, disease‐free interval <6 months. 64% of patients reached cetuximab RDI ≥80%; mean cetuximab RDI was 88%. 46% of patients received maintenance cetuximab (mean RDI, 91%). Median progression‐free survival and overall survival were 4.5 and 9.4 months. No new/unexpected safety findings were observed. Conclusions: The DIRECT study showed that first‐line cetuximab plus PBT was a feasible, beneficial first‐line treatment regimen in patients with R/M SCCHN in the real‐world setting.